Navigating the Evolving Treatment Paradigm for _EGFR_-Mutant NSCLC - Sebastian Kraus (healthbook TIMES. Oncology Hematology)
In non-small cell lung cancer (NSCLC), the most prevalent driver mutations in epidermal growth factor receptor (_EGFR_) are deletions in exon 19 (Ex19del) and L858R mutations in exon 21, which comprise approximately 90% of all _EGFR_ mutations. In contrast, exon 20 insertion (Ex20ins) mutations are relatively rare, accounting for up to 12% of _EGFR_ mutations and ranking third in frequency. Given the many treatment options available for NSCLC and the increasing understanding of the interactions between mutations and common therapies in the palliative stages, comprehensive next-generation sequencing (NGS) is recommended at the initial stage, particularly for adenocarcinomas. _EGFR_ Ex20ins mutations are a molecularly heterogeneous group of over 100 variants that are identified through NGS using tumor DNA. The high prevalence of these _EGFR_ mutations in NSCLC has led to significant research efforts aimed at optimizing therapeutic options for patients. This review article highlights the key findings from recent studies in the field of _EGFR_ mutations in NSCLC.